Memoirs of Vaidyas The Lives and Practices of Traditional Medical Doctors in Kerala, India III - T SUTOMU Y AMASHITA and P. R AM MANOHAR (eJournal of Indian Medicine, 2007)
This article presents an English translation of an interview with a doctor of traditional Indian medicine (Āyurveda), paediatrician, G*** Vaidyar (1935~) in Kerala, India. The contents of the interview are: 1. Tradition of the family and the manufacturing of medicines; 2. Medical texts and manuscripts; 3. Methods of learning Āyurveda; 4. Modern Āyurveda; 5. Diseases in Kerala; 6. The future of Āyurveda.